2007
DOI: 10.1097/01.sla.0000232539.88254.80
|View full text |Cite
|
Sign up to set email alerts
|

Early Endoscopic Intervention Versus Early Conservative Management in Patients With Acute Gallstone Pancreatitis and Biliopancreatic Obstruction

Abstract: The present study failed to provide evidence that early endoscopic intervention reduces systemic and local inflammation in patients with acute gallstone pancreatitis and biliopancreatic obstruction. If acute cholangitis can be safely excluded, early endoscopic intervention is not mandatory and should not be considered a standard indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(24 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Charles et al believes that all cases of suspected gallstones pancreatitis with known or suspected choledocholithiasis should undergo systematic biliary sphincterotomy [17]. In contrast, Alejandro et al reported that early endoscopic intervention failed to reduce systemic and local inflammation in patients with AGP and biliopancreatic obstruction [18]. Early endoscopic intervention is not required if acute cholangitis can be safely excluded and should not be considered a standard indication.…”
Section: Discussionmentioning
confidence: 99%
“…Charles et al believes that all cases of suspected gallstones pancreatitis with known or suspected choledocholithiasis should undergo systematic biliary sphincterotomy [17]. In contrast, Alejandro et al reported that early endoscopic intervention failed to reduce systemic and local inflammation in patients with AGP and biliopancreatic obstruction [18]. Early endoscopic intervention is not required if acute cholangitis can be safely excluded and should not be considered a standard indication.…”
Section: Discussionmentioning
confidence: 99%
“…The role of early ERCP in the context of choledocholithiasis has also been evaluated in prospective studies [ 61 , 70 - 74 ]. Amongst 153 patients in a multicenter prospective study, patients were divided into 2 groups (with and without signs of cholestasis) [ 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although ERCP was associated with fewer complications than the observation group (25% vs. 54%, p = 0.02) in patients with signs of cholestasis, mortality was not significantly lower (6% vs. 15%, p = 0.2). Additionally, ERCP neither reduced complications (45% vs. 41%, p = 0.8) nor mortality (14% vs. 17%, P = 0.7) in patients without cholestasis, suggesting that ERCP should be indicated only in selected patients with persistent cholestasis [ 61 , 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous animal and human studies suggested that duration of obstruction over 48 hours may probably result in pancreatic necrosis [ 10 – 13 ]. With regard to this point of view, any measure that can relieve ampullary obstruction as soon as possible is a crucial part in minimizing the subsequent local or systemic complications [ 14 ].…”
Section: Introductionmentioning
confidence: 99%